Effect of whole-body contrast-water therapy on recovery from intense exercise of short duration - Sayers, M. G.; Calder, A. M.; Sanders, G. G. (European Journal of Sport Science, 2011)
Athletes often use contrast-water therapy as a recovery modality to reduce training fatigue. However, there is debate regarding the effectiveness of this practice, particularly when active and passive recovery regimens are more readily accessible. Fourteen male state-level hockey players participated in three experimental sessions involving two 30-s maximal-intensity Wingate ergometer tests interspersed by a 12-min recovery period. Three different recovery protocols were assessed. Passive recovery involved sitting while active recovery comprised low-intensity cycling. Contrast-water therapy recovery involved three cycles of alternate immersion in heated (38°C) and cool (15°C) water for 3.5 min and 30 s respectively. Heart rate, blood lactate concentration, and ratings of fatigue were assessed immediately before (baseline) and after the first Wingate test, 3 min and 7 min into and at the end of the recovery period, and immediately after the second Wingate test. Blood pressure was assessed at baseline, immediately before recovery, and immediately after recovery. Heart rate remained elevated 3 min and 7 min into as well as after active recovery compared with both contrast-water therapy (P<0.001) and passive recovery (P<0.001), and was elevated 3 min into and after contrast-water therapy recovery compared with passive recovery (P<0.001). Blood lactate concentration was significantly lowered 7 min into and after active recovery (P<0.001) and contrast-water therapy (P<0.001) compared with passive recovery, but no significant difference was observed between active recovery and contrast-water therapy. Rating of fatigue was significantly lower for contrast-water therapy (P<0.001) compared with passive recovery and active recovery, the latter two being similar. However, no significant differences were found between the recovery modalities for any of the test or retest Wingate performance indices. Although contrast-water therapy offered similar benefits to well-established active recovery protocols, it also resulted in reduced ratings of fatigue and a faster return to baseline for some variables. Although restricted to a limited time frame, these findings reflect that the subtle effects from contrast-water therapy may translate to important practical differences that can influence the recovery choices of athletes, particularly when engaged in intense events/training where the recovery period is limited.